PERAN PEREMPUAN DALAM PENINGKATAN EKONOMI MASYARAKAT DI DESA TEGAL MAJA KECAMATAN TANJUNG, KABUPATEN LOMBOK UTARA: The Role Of Women In Improving The Community's Economy In Tegal Maja Village, Tanjung District, North Lombok Regen - Gugun Saputra (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Women's freedom to innovate and express themselves in this era has both positive and negative impacts. A positive impact is that women can be independent in meeting their economic needs, either as employees or as traders. The purpose of this study is to determine the role of women in improving the community's economy in Tegal Maja Village, Tanjung District, North Lombok Regency. This research is a survey with a qualitative approach. Data collection was conducted through direct observation, interviews, and documentation. The results show that women contribute to the household economy. Women's involvement in gardening activities also plays a role in strengthening family food security. By managing productive gardens, women ensure the availability of sufficient local food and improve the family's nutritional quality through fresh food consumption. Women's role in gardening activities in Tegal Maja Village also encourages local economic empowerment through the utilization of existing resources and skills. Production activities, simple processing, and marketing of garden produce provide women with experience in business management, market negotiations, and household income management.